A Relational Dialectic Analysis in the Discourse of Life Choices of Professional Women - Yulfa Margiana; Izzati Rizal (Journal of Communication, Sustainability, and Empowerment, 2026)
This study aims to understand the relational dialectics perspective in the discourse of professional women's life choices. This research employs a qualitative approach with interview and observation methods. The results show that several factors influence professional women's decisions to delay marriage, including the Sandwich Generation, career, and mental readiness. This study finds that professional women prioritize their role as family supporters, economic stability through their careers, and mental readiness before deciding to get married. These findings provide insight into the relational dynamics of professional women in making decisions about their life choices.